A study on a low-cost real time MEMS based modular Indoor Environmental Quality monitor sensor - Nanos Nikos; Lee Andreas; Mavridou Theodora (E3S Web of Conferences)
Indoor air quality (IAQ) is crucial for human well-being, particularly in urban environments where individuals spend most of their time indoors. Poor IAQ, influenced by pollutants like CO2, particulate matter (PM), and volatile organic compounds (VOCs), necessitates real-time monitoring for effective mitigation. Traditional IAQ monitoring systems, while precise, are often costly and cumbersome, limiting accessibility. This study explores the feasibility of integrating low-cost micro-electromechanical systems (MEMS) sensors with Arduino platforms to develop an affordable, portable IAQ monitoring solution. A prototype IAQ monitoring system was developed using MEMS sensors, including the BME680 for temperature, humidity, and VOCs; LM358 for sound levels; BH1750 for light intensity; GP2Y10x and SPS30 for PM detection. The system was integrated with an Arduino MKR1010, enabling real-time data logging and wireless transmission. Calibration against commercial sensors ensured data validity. The prototype sensor package underwent preliminary deployments in controlled and dynamic environments, including an indoor laboratory and a concrete lab. Results demonstrated the system’s ability to capture variations in IAQ parameters accurately. Despite minor limitations, the system proved viable for continuous IAQ monitoring at a significantly reduced cost compared to traditional systems. Future work will focus on refining sensor calibration, improving data processing through advanced analytics, and establishing standardized evaluation criteria to enhance sensor reliability and potential use framework.